83=-3x-5(2x-1)

Simple and best practice solution for 83=-3x-5(2x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 83=-3x-5(2x-1) equation:


Simplifying
83 = -3x + -5(2x + -1)

Reorder the terms:
83 = -3x + -5(-1 + 2x)
83 = -3x + (-1 * -5 + 2x * -5)
83 = -3x + (5 + -10x)

Reorder the terms:
83 = 5 + -3x + -10x

Combine like terms: -3x + -10x = -13x
83 = 5 + -13x

Solving
83 = 5 + -13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '13x' to each side of the equation.
83 + 13x = 5 + -13x + 13x

Combine like terms: -13x + 13x = 0
83 + 13x = 5 + 0
83 + 13x = 5

Add '-83' to each side of the equation.
83 + -83 + 13x = 5 + -83

Combine like terms: 83 + -83 = 0
0 + 13x = 5 + -83
13x = 5 + -83

Combine like terms: 5 + -83 = -78
13x = -78

Divide each side by '13'.
x = -6

Simplifying
x = -6

See similar equations:

| r(r-6)=7 | | 150=-6(4x-5) | | 4cos^2x-6cosx+2=0 | | (3-2i)+(-5+3i)=0 | | 289u^2-1=0 | | t^2-2t=3t+24 | | 8p+p^2=-16 | | -68=-4a-4(5-3a) | | 3x+11y-2=0 | | -16t^2+28t+6=0 | | -6(-2x+6)=-108 | | 10x+2=180-4x-4 | | 30x^2-120=-50x | | 4(a^2+18a+81)=120 | | ln(x^2+8)=6 | | E/-9=6 | | 125=5(5k-4) | | 1.05/1.26=x/.36 | | X=-3(4)+20 | | ln(-499.2)= | | -74=6+4(6m+4) | | 12t^2-164t-56=0 | | -25+15w=200 | | (.25x+3)=(.75x-7) | | (7x-5)/7 | | x/.36=1.05/1.26 | | (x1/2*x1/2)/x | | 4s-29=-23+6s | | 70=5(6-4v) | | 7x-5/7 | | (7-x)=0.5 | | 4s-29=23+6s |

Equations solver categories